Pengembangan Dakwah di Majelis Taklim Desa Balai Makam Kecamatan Bathin Solapan Kabupaten Bengkalis - Putri Kembar Kembar (STAI Hubbulwathan Duri, 2021)
As a center of Islamic learning, it is recognized has donated a very large role in the intellectual life, especially in the teaching of religious and moral strengthening of the nation. Its existence in society has brought benefits and welfare for the people, especially for women who become members and congregation. Development of Dakwah is one of managerial behaviors that is included training used as a means to improve somene’s skills and facilitate an adjustment to the work and his carierr. Majelis Taklim in improving the management of the organization includs of the development and improvement in the Dakwah mission in community. To be able to do the development and improvement of Dakwah, it must be able to reform and innovation to strengthen the resources of members and conduct design strategies and approache appropriate and effective Dakwah with variative and participative media communication.